SEMIOTIC ANALYSIS ON SELECTED OPPO SMARTPHONE’S ADVERTISEMENTS - Eka Margianti Sagimin; Anisa Linda Priyani (Makassar State University, 2018)
This study is attempted to explain and analyze the semiotic process and the messages implied on Oppo Smartphone’s advertisment. The semiotic approach is used to identify and to analyze the data which focuses on Representament, Object and Interpretant by using Triadic Semiosis Concept of C.S. Pierce’s theory. The objective of this study is to analyze how semiosis proses occurs and to interpret the messages conveyed by the sign in Oppo Smartphone’s Advertisement. The study employed descriptive qualitative as the data were collected in the form of written words which produce the descriptive information. Based on the result finding, there are five advertisments of Oppo’s selected advertisments; Oppo F1,F5,N1 Mini, R1 and R5. Those advertisments have hidden messages which make the viewers or customers unable to catch the messages properly. From the result analysis, it can be affirmed that all aspects in the advertisments have the same messages to persuade the readers to buy the product even though the sign in each advertisement is different.